2023
DOI: 10.3390/biomedicines11061574
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Muscle Mass and Strength on Bone Mineralisation with Consideration of Sclerostin Concentration

Abstract: Osteoporosis is a disease characterised by a reduction in bone strength due to increased porosity and impaired mineralisation. In our study, we investigated whether muscle strength and mass exert a significant effect on bone mineral density in young adult women. We also tested whether sclerostin can be used as an indicator in the assessment of bone mineralisation. The study included 111 patients. All patients had their bone mineral density determined in the L1–L4 section of the lumbar spine and in the whole sk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…Consistent with the findings in patients with a fresh hip fracture [ 26 ] or hematological disorders undergoing 1-year glucocorticoid therapy (> 7.5 mg/day) [ 15 ], as well as in mice exposed to endogenous and exogenous glucocorticoids [ 14 ], we identified significant positive correlations between circulating sclerostin levels and BMD measurements in postmenopausal females with GIO. These studies suggest that sclerostin concentration might serve as a complementary or potentially alternative indicator to densitometric testing [ 2 , 23 , 24 ]. One suggested rationale for this positive association between sclerostin and BMD posits that circulating sclerostin levels are contingent upon the number and activity of osteocytes, theoretically correlating with the overall bone mass [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Consistent with the findings in patients with a fresh hip fracture [ 26 ] or hematological disorders undergoing 1-year glucocorticoid therapy (> 7.5 mg/day) [ 15 ], as well as in mice exposed to endogenous and exogenous glucocorticoids [ 14 ], we identified significant positive correlations between circulating sclerostin levels and BMD measurements in postmenopausal females with GIO. These studies suggest that sclerostin concentration might serve as a complementary or potentially alternative indicator to densitometric testing [ 2 , 23 , 24 ]. One suggested rationale for this positive association between sclerostin and BMD posits that circulating sclerostin levels are contingent upon the number and activity of osteocytes, theoretically correlating with the overall bone mass [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, Patalong-Wojcik and collaborators found no discernible disparity in sclerostin levels between groups with normal and diminished BMD. Moreover, there was an absence of correlation between sclerostin concentration and lumbar vertebrae BMD in young adult women [ 2 ]. The observed disparity could potentially be attributed to variations in population characteristics, including factors such as gender, menopausal status, and notably, the age range of the study cohort.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another mechanism is to scavenge free oxygen molecules required to initiate ROS production and create long-term genomic effects for the down-regulation of genes encoding pro-oxidant enzymes [39,40]. Some of the in-vivo studies have shown relationships between LPS and bone structures; deterioration of bone structure has been revealed with LPS exposure [19,32,[34][35][36]. Droke et al showed that negative effects of LPS induced alterations in bone structure, and these effects upregulated the TNF-α expression in the tibia metaphyseal region [32].…”
Section: Discussionmentioning
confidence: 99%
“…Some of these proteins are secreted by osteocytes and one of their main roles is to provide bone modeling and remodeling. Sclerostin, which is expressed and secreted in osteocytes and other terminally differentiated cell types embedded inside mineralized matrices, suppresses osteoblastic bone production, and PHEX, another osteocyte-specific protein, is linked to biomineralization and phosphate homeostasis [18][19][20]. MEPE has an important role in bone mineralization and maintains the balance of mineralization in the osteocyte environment, especially against mechanical loading [21].…”
Section: Introductionmentioning
confidence: 99%